Dialectics of Cultural Production: Branding Indigo-Dyed Textiles in Sakon Nakhon, Thailand - Chanjittra Chanorn (2019)
© 2018, © 2018 Informa UK Limited, trading as Taylor & Francis Group. This article explores the processes of cultural production of indigo-dyed textiles and their distribution and consumption, examining how commodities “mediate” people and their practices and relations in different places and contexts. The dynamics of cultural production as presented in the life cycle of a product form part of a brand’s social life that accretes to comprise its “cultural-economic biography.” The brand is designed, negotiated, and experienced by producers, customers, and other actors throughout its social life. The brand is also perceived by audiences in terms of the cultural-economic biography of the different products under the brand umbrella. I undertook ethnographic research in Sakon Nakhon Province, Thailand, and used the “social life of things” method to highlight the commoditization processes of indigo-dyed textiles.